Exploring the three-dimensional flow-sediment dynamics and trapping mechanisms in a curved estuary: The role of salinity and circulation - Tao, Jianfeng; Zhu, Renjie (Frontiers in Marine Science, 2022)
Combined with the observed data in the wet season in June 2015, structures of longitudinal and lateral residual current and characteristics of the estuarine turbidity maximum (ETM) in the Yongjiang estuary (YE) are studied using a three-dimensional baroclinic flow and sediment numerical model. The mechanisms of residual current and sediment trapping are investigated according to the momentum balance analysis and sediment transport decomposition. The results show that at spring tide, the outflowing longitudinal residual current is dominated by longitudinal advection and barotropic pressure gradient. At neap tide, a remarkable baroclinic effect emerges at the bottom of the river mouth area, driving the landward residual current and forming the estuarine circulation. Lateral residual current at upstream bends with lower salinity is dominated by longitudinal advection and barotropic pressure gradient. The flow directs toward the concave bank at the surface and toward the convex bank near the bottom at these sections. At downstream bends with higher salinity, the lateral residual current is greatly affected by the baroclinic gradient, which will shift the lateral flow circulation structure. In transition straight reaches located at Qingshuipu and Zhenhai, the lateral residual current presents a double-cell circulation with surface convergence and bottom divergence. During spring tide, the ETM is located near Qingshuipu, driven by landward tidal pumping transport due to the strong tidal energy. During neap tide, a strong exchange flow generates landward circulation transport around the river mouth, and the ETM moves downstream to Zhenhai. At bends, sediment along the cross section is laterally trapped on the convex bank, driven by bottom lateral flow induced circulation transport. While in transition straight reaches, high turbidity is still concentrated in the deep groove, caused by bottom divergent flow and circulation transport.